A Game for Simulating the Sucessfull Saga of an Individual Micro Entrepeneur - Parreiras, Marcus; Marques, Pedro; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento Digital, 2022)
This article presents The MEI Game, a videogame implemented as an educational visual novel based on a real story about the creation and management of a small business in Baixada Fluminense. This game provides an entrepreneurship scenario, which ends with the success or failure of the business, based on the player’s decisions. From its feedback, users can understand the reasons for their results, and retrace their steps to fix their errors, reinforcing their understanding of the theory.